Coccomyxa antarctica sp. nov. from the Antarctic lichen Usnea aurantiacoatra - Cao, Shunan; Zhang, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Peng, Fang; Zhou, Qiming (PhytoKeys, 2018)
The single celled green alga Coccomyxa antarctica Shunan Cao & Qiming Zhou, sp. nov. was isolated from the Antarctic torrential lichen Usnea aurantiacoatra (Jacq.) Bory. It is described and illustrated based on a comprehensive study of its morphology, ultrastructure, ecology and phylogeny. C. antarctica is a lichenicolous alga which has elongated cells and contains a parietal chloroplast as observed under the microscope. C. antarctica is clearly different from other species by phylogenetic analysis (ITS rDNA and SSU rDNA sequences), also it differs from its phylogenetic closely species C. viridis by its larger cell size.